Comparison between Microsurgical Subinguinal Varicocelectomy with and without Testicular Delivery for Infertile Men: Is Testicular Delivery an Unnecessary Procedure? - Hou, Yi; Zhang, Ying; Zhang, Yun; Huo, Wei; Li, Hai (Urology Journal, 2015)
Purpose: Controversy still exists as to whether testicular delivery during microsurgical subinguinal varicocelectomy (MSV) provides benefit to the patient or not. This study specifically compared the therapeutic effect of MSV with and without testicular delivery for the treatment of varicocele in a cohort of infertile men. Materials and Methods: We conducted a prospective, randomized, controlled study to evaluate the therapeutic efficacy of MSV with and without testicular delivery for the treatment of varicocele in infertile men. A total of 100 patients were specifically recruited using strict inclusion criteria to undergo MSV with testicular delivery (group1, n = 50) or MSV without testicular delivery (group 2, n = 50). All patients were followed-up at 3, 6 and 12 months following surgery. Semen parameters, pregnancy and recurrence rates, and complications were monitored. Results: Mean surgical time for group 1 was significantly longer than group 2 (90.50 ± 15.60 min vs. 84.30 ± 15.58 min; P = .001). Sperm count and motility were significantly improved at the 12-month follow-up appointment in both groups compared with pre-operative values, but were not significantly different at 3, 6, and 12 months when compared between the two treatment groups. The incidence of scrotal edema, and spermatic/testicular engorgement were higher in group 1 (both P = .001), although natural pregnancy rate was not significantly different between the two groups at the 12 month follow-up appointment (46% vs. 42%) (P = .817). Conclusion: MSV with testicular delivery did not reduce the risk of recurrence and led to improved semen quality compared with MSV without testicular delivery. However, there was a higher risk of complication with this technique, which must be borne in mind when considering the clinical implications of our dataset.